Correlation between bacteriophage chi adsorption and mode of flagellar rotation of Escherichia coli chemotaxis mutants. - Ravid, S (1983)
We studied the adsorption of phage chi to various behavioral mutants (che mutants) of Escherichia coli having different swimming modes. Bacteriophage chi infects only bacteria with active flagella, and it was therefore of interest to examine whether the mode of swimming has an effect on the susceptibility of the bacteria to the phage. Neither the mode of swimming (smooth swimming or tumbling) nor the direction of flagellar rotation affected the degree of chi adsorption to the bacterial cells. Furthermore, the tumbling frequency, the rotation speed (tethered cells of all of the strains examined had the same average speed of rotation), the time proportion of rotation, and the reversal frequency were not important in determining susceptibility to chi. The only variable that influenced chi adsorption was the fraction of the population whose flagella rotated incessantly. A direct, linear correlation was found between chi adsorption and the fraction of unceasing rotation in each population. It seems, therefore, that an individual bacterium whose flagella pause periodically and briefly during rotation is not susceptible to irreversible adsorption of the phage. Pausing of rotation thus seems to be a new feature of motility that is prevalent especially in che mutants. It is concluded that irreversible chi adsorption can serve as a quantitative assay only for incessant flagellar rotation of E. coli.